2012
DOI: 10.1016/j.jnoncrysol.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of glass properties during a substitution of S by Se in Ge28Sb12S60−xSex glass network

Abstract: In this paper, a detailed study to examine the influence of chalcogen S/Se mole % in the Ge 28 Sb 12 S 60 −x Se x glass system, with x = 0, 15, 30, 45 and 60, is presented that provides insight into the effect of chalcogen content on the glass network and properties. Specifically, we report results of a systematic study to evaluate the relationship between compositional variation, glass properties and dominant bonding configurations. These materials are important to applications in optics manufacturing where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The primary intense peaks in the irradiated film at 148 cm –1 (A 2 2u mode) and 252 cm –1 are linked to the Sb–Sb bond in the (Se 2 ) Sb–Sb (Se 2 ) structural unit. Similarly, the 198 cm –1 peak denotes the heteropolar Se–Sb bond stretching mode in (SbSe 3/2 ) pyramids connected through a bridging Se. , Among all ion-irradiated films, we observe that the weakly ion-irradiated film, i.e., 5 × 10 15 ions/cm 2 , shows a higher intensity, which shows more structural changes in the film and decreased with a further increase in ion dose. Proton irradiation results in the breaking of weaker homopolar bonds such as Se–Se bonds and creates comparatively stronger (SbSe 3/2 ) pyramidal units with a slight shift in wavenumber, which results in a decrease in disorder in the system and enhancement of the optical energy gap.…”
Section: Resultsmentioning
confidence: 69%
“…The primary intense peaks in the irradiated film at 148 cm –1 (A 2 2u mode) and 252 cm –1 are linked to the Sb–Sb bond in the (Se 2 ) Sb–Sb (Se 2 ) structural unit. Similarly, the 198 cm –1 peak denotes the heteropolar Se–Sb bond stretching mode in (SbSe 3/2 ) pyramids connected through a bridging Se. , Among all ion-irradiated films, we observe that the weakly ion-irradiated film, i.e., 5 × 10 15 ions/cm 2 , shows a higher intensity, which shows more structural changes in the film and decreased with a further increase in ion dose. Proton irradiation results in the breaking of weaker homopolar bonds such as Se–Se bonds and creates comparatively stronger (SbSe 3/2 ) pyramidal units with a slight shift in wavenumber, which results in a decrease in disorder in the system and enhancement of the optical energy gap.…”
Section: Resultsmentioning
confidence: 69%
“…According to the molecular model [39], each Sb atom in the Sn-Sb-S ternary compound is covalently The band situated at 163 cm -1 can be assigned to stretching modes of Sn-tetrahedral units [40,41]. Other authors reported that this peak (163 cm -1 ) corresponds to a vibration related to the presence of Sb-Sb linkages [42]. Hence, the vibration band around 163 cm −1 in Sn 2m-4 Sb 4 S 2m+2 (m = 2.5, 3 and 4) could be the combined effect of the stretching modes of Sntetrahedra and Sb-Sb linkages.…”
Section: Discussionmentioning
confidence: 99%
“…4(b). The glass transition temperature defined by the viscosity occurs at approximately 285°C (10 12 Poise) while the Littleton point, the point at which a glass deforms under its own weight, occurs at approximately 340°C (10 7.6 Poise) [39,50]. The waveguide geometry remains intact at temperatures below 285°C and deforms completely as the temperature approaches 340°C.…”
Section: Waveguide Fabrication and Characterizationmentioning
confidence: 99%